2009
DOI: 10.3844/ajassp.2009.1860.1867
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Concentrations of Dissolved Oxygen and Chlorophyll-a in the Coastal Waters of Babolsar

Abstract: Problem statement: Dissolved Oxygen (DO) and Chlorophyll-a (Chl-a) are two vital requirements for marine ecosystems. Nowadays, discharge of large amounts of industrial, agricultural and urban wastes threats the Caspian Sea (CS) environment. With regard to the elevation of nutrient contents, average of DO concentrations in the deeper layers of the CS is reducing. On the other hand, increased amounts of phytoplankton in water bodies in reaction to the enhancement of nutrient supply can have severely damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Moreover, Nasrollahzadeh et al (2008a) and Bagheri et al (2010) observed an increase in phytoplankton abundance in 2001-2002 and 2005 as compared to previous years. According to Khodaparast (2006) and Makaremi et al (2007) (Khodaparast, 2006;CEP, 2006;Jamshidi et al, 2009). In the Caspian Sea, the fauna that have developed there are largely endemic and are therefore particularly susceptible to external influences (Dumont, 1998).…”
Section: Inrtoductionmentioning
confidence: 99%
“…Moreover, Nasrollahzadeh et al (2008a) and Bagheri et al (2010) observed an increase in phytoplankton abundance in 2001-2002 and 2005 as compared to previous years. According to Khodaparast (2006) and Makaremi et al (2007) (Khodaparast, 2006;CEP, 2006;Jamshidi et al, 2009). In the Caspian Sea, the fauna that have developed there are largely endemic and are therefore particularly susceptible to external influences (Dumont, 1998).…”
Section: Inrtoductionmentioning
confidence: 99%